PENGARUH SIKAP KONSUMEN PADA IKLAN BERTEMA RAMADHAN MARJAN DAN BRAND IMAGE SIRUP MARJAN TERHADAP BRAND LOYALTY SIRUP MARJAN - Gabriel Antonio Chiesa Lumban Tobing; Djoko Setyabudi (Interaksi Online, 2026)
Competition in the syrup industry in Indonesia is increasingly intense, particularly during Ramadan. Although Marjan Syrup remains a top-of-mind brand, it has experienced a decline in its Top Brand Index and market share, indicating a gap between positive consumer attitudes toward advertising and brand image and actual brand loyalty. This study aims to analyze the influence of consumer attitudes toward Ramadan-themed advertisements and brand image on brand loyalty. This research employs a quantitative approach with an explanatory design, involving 100 respondents who have consumed Marjan and been exposed to its advertisements. Data were analyzed using simple linear regression after passing validity, reliability, and classical assumption tests. The results show that both attitudes toward advertising and brand image have a positive and significant effect on brand loyalty. The more positive consumers’ perceptions, the higher the likelihood of repurchase, recommendation, and brand preference. These findings confirm that brand loyalty is shaped not only by cultural associations but also by effective advertising communication and consistent brand image.